Autonomic symptoms are predictive of dementia with Lewy bodies. (February 2022) - Hu, Wenzheng; Liu, Shuai; Wang, Fei; Zhu, Han; Du, Xiaoshan; Ma, Lingyun; Gan, Jinghuan; Wu, Hao; Wang, Xiaodan; Ji, Yong
Abstract: Introduction: Autonomic symptoms are common in patients with dementia with Lewy bodies (DLB). Although autonomic dysfunction is considered as one of the primary early markers in patients with DLB, there are few studies that examine the timing of the onset of autonomic symptoms in these patients. The purpose of the current study was to evaluate the time of onset of autonomic symptoms in patients with DLB using a questionnaire. Methods: Autonomic symptoms were evaluated in patients with DLB using the Scales for Outcomes in Parkinson's disease - autonomic (SCOPA-Aut) questionnaire. Time of the onset of autonomic symptoms of patients with DLB was also assessed relative to that of memory loss. Results: A total of 106 patients with DLB were included. The most frequent symptom of dysautonomia in patients with DLB was constipation (60.4%), followed by orthostatic dizziness (33%), urinary frequency (30.2%), and daytime hyperhidrosis (22.6%). The gastrointestinal system was the most prominent system of autonomic dysfunction in patients with DLB. Orthostatic dizziness, daytime hyperhidrosis, and constipation all preceded the onset of memory loss by 0.2 ± 4.9, 3.3 ± 8.6, and 3.7 ± 9.2 years, respectively, while urinary incontinence occurred 1.7 ± 1.5 years following the onset of memory loss. Conclusion: Many autonomic symptoms precede the onset of memory loss in patients with DLB, especially constipation and daytime hyperhidrosis. These symptoms can facilitate an early diagnosis of patients with DLB. Highlights: Many autonomic symptoms precede the onset of memory loss in DLB patients, especially constipation and daytime hyperhidrosis. The gastrointestinal system is the most prominent system of autonomic dysfunction in individuals with DLB. Constipation is the most common symptom of autonomic dysfunction in individuals with DLB.